Experimental and theoretical study on the effect of inclined angle in the SCR pipe-in-pipe system. (15th April 2018) - Wang, Wenming; Li, Haoran; Chen, Yingchun; Peng, He
Abstract: A novel method of pipeline pigging is that Coiled Tubing (CT) connected with a pig, and then CT is injected into the SCR to clean up pipelines. The CT needs enough axial force so that it would not be stuck in the SCR during the pipeline pigging operation. To analyze the axial load transfer characteristic, paper built the force analysis of the micro element on the straight and curved section, amended effective axial force and the friction between the CT and SCR, and built the mathematical model of SCR pipe-in-pipe system considering impacts of the coiled tubing's buckling. The axial force of the random micro section can be calculated through iterative method. In order to verify the correctness of the theory, the SCR pipe-in-pipe system's indoor platform was built. The experimental platform can study different effects which affect the CT's load transfer behavior within the unfixed SCR. The experimental results of two different phases which inclined angles were 2.0° and 30.0° show that CT's transfer efficiency of axial load is less than 85.0% in SCR pipe-in-pipe system, and it will increase with the inclined angle increasing. Through comparing experimental and theoretical calculation results, the mathematical model of SCR pipe-in-pipe system is validated. Paper calculated the axial force results on the inclined angle 2.0°, 10.0°, 18.0°, 26.0° and 30.0° by the theoretical mechanical model. The theoretical calculation results show that the transfer efficiency would increase with the increasing of the inclined angles. To ensure more axial force to be transferred to the CT's bottom-end, the inclined angle should be as big as possible. The above research can provide theoretical support to the SCR's pigging operation. Highlights: We discussed the force analysis on the straight and curved section of the CT considering impacts of the coiled tubing's buckling.. Paper conducted two different phases which inclined angles were 2° and 30°. The mechanical model is validated through comparing the experimental and theoretical calculation results. The calculation results show that the transfer efficiency would increase with the increasing of the inclined angles.